Bahasa Inggris - Rukin Rukin (Jurnal Ilmu Sosial dan Humaniora, 2025)
This study examines the economic impacts of marine resource management on coastal populations, with an emphasis on sustainable development, governance frameworks, and community empowerment. Employing qualitative methods including in-depth interviews, focus group discussions (FGDs), and thematic analysis the research explores how inclusive, gender-responsive governance fosters equitable resource distribution and local participation. While marine resource management can improve livelihood security, ecosystem health, and socio-economic stability, implementation is often impeded by institutional fragmentation, policy misalignment, and weak stakeholder coordination. Findings underscore the need for multilevel collaboration among local governments, coastal communities, and external actors to address these structural constraints. Furthermore, adaptive management, continuous monitoring, and the integration of local ecological knowledge are pivotal to long-term sustainability. The study argues that governance models must holistically incorporate socio-economic and environmental dimensions to advance the sustainable development goals (SDGs) in coastal regions. By offering empirical insights into the interplay between governance and coastal resilience, this research advances the theoretical discourse on participatory resource management. This study contributes to the development of inclusive marine governance models relevant to Southeast Asia and other archipelagic regions.